Alcohol Vapor Post‐Annealing for Highly Efficient Sb2S3 Planar Heterojunction Solar Cells. Issue 8 (10th July 2019) - Han, Jian; Wang, Shuangjie; Li, Xuanhua; Tang, Huijie; Cao, Qi; Yang, Jiabao; Zhu, Jinmeng; Liu, Xingrui; Li, Zhen; Liu, Weimin
Abstract : Solution‐processed Sb2 S3 planar heterojunction solar cells have shown great progress in power conversion efficiency (PCE) in recent years. However, a conventional solution process yields Sb2 S3 films with a small grain size. Herein, an alcohol vapor post‐annealing strategy is reported that uses alcohol vapors to facilitate grain growth of Sb2 S3 films during annealing, achieving films with a larger grain size and better crystallinity. A series of alcohols with different polarities are used for the vapor post‐annealing. Methanol with the highest polarity provides films with the largest grain size. As a result, the Sb2 S3 films prepared via vapor post‐annealing show enhanced light absorption, longer carrier lifetime, and less carrier recombination, which are verified by photoluminescence, transient photovoltage, suns‐short‐circuit photocurrent density, and suns‐open‐circuit voltage measurements. The Sb2 S3 solar cells post‐annealed with methanol vapor exhibit a PCE of 5.27%, showing a drastic improvement of 31% compared with the non‐treated devices. The alcohol vapor post‐annealing approach presents a new avenue toward controlling the morphology and crystallinity of solution‐processed Sb2 S3 films and achieving efficient Sb2 S3 solar cells. Abstract : The alcohol vapor post‐annealing treatment on Sb2 S3 films is demonstrated as an effective method for high‐performance Sb2 S3 planar heterojunction solar cells. Due to the higher polarity of methanol compared with that of ethanol and isopropanol, the meth‐annealed Sb2 S3 devices show a power conversion efficiency of 5.27%, with an increase in 31% compared with the control device.